Management Implementation In Educational Organizations (Case Study At Smp It Ruhul Islam Simeulue Aceh) - Syahrul Amin. ZD (PT Inovasi Pratama Internasional, 2025)
This study is entitled Implementation of Management in Educational Organizations (Case Study at SMP IT Ruhul Islam Simeulue Aceh). The purpose of this study is to determine the implementation of educational management in schools experiencing management problems. This research was conducted at SMP IT Ruhul Islam in Simeulue Regency, Aceh, using a qualitative method with pedagogical and sociological approaches. Data were collected through interviews, observations, and documentation, with informants selected using purposive and snowball sampling techniques, including the principal, teachers, students, parents, and school committee. The results show that the implementation of school management faces various challenges, including suboptimal use of human resources, declining student competitiveness, and limited management effectiveness. Although support from parents with middle-to-upper economic backgrounds helps provide facilities, the school still faces risks due to economic disparities and its temporary infrastructure status. The study also found that the decline in school performance since 2019 was influenced by the COVID-19 pandemic, particularly due to the unpreparedness of school leadership in managing online learning. Strengthening discipline, improving management quality, and optimizing resources are essential to enhance graduate competitiveness.